Pengaruh Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Melalui Orientasi Kewirausahaan Individu Sebagai Variabel Mediasi Pada Mahasiswa Pendidikan Fakultas Ekonomika Dan Bisnis Universitas Negeri Surabaya - Sofiani, Rosandra Vichi; Subroto, Waspodo Tjipto (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Indonesia is a country with a high unemployment rate, including among fresh graduates. This of course must be handled, one of which is by developing an entrepreneurial spirit. Every person who has the determination and desire to become an entrepreneur will be useful in opening up employment opportunities, thereby reducing the unemployment rate. Opening job opportunities can be done by anyone who has the opportunity to take advantage of opportunities, including students. This research aims to determine the influence of entrepreneurship education on interest in entrepreneurship through individual entrepreneurial orientation in students. The sample in the research was 155 students from the Education Study Program, Faculty of Economics and Business, Surabaya State University, class of 2020. The analysis technique used in this research was Structural Equation Modeling (SEM) using SMART-PLS software. The results of this research show that directly the exogenous variable, namely entrepreneurship education, has a significant effect on interest in entrepreneurship, and indirectly, individual entrepreneurial orientation succeeds in mediating the relationship between the exogenous variable entrepreneurship education and the endogenous variable interest in entrepreneurship.